The Influence of Organizational Culture and Transformational Leadership on Employee Performance at PT PLN (Persero) South Sumatera, Jambi and Bengkulu - Mochammad Iqbal Wahab; Ratri Wahyuningtyas (Riset Akuntansi dan Bisnis Indonesia, 2025)
Purpose: This study examines how organizational culture and transformational leadership affect employee performance at PT PLN (Persero) South Sumatra, Jambi, and Bengkulu. Methodology/approach: This study used a quantitative approach involving 288 employees of PT PLN (Persero) in South Sumatra, Jambi, and Bengkulu, selected using total sampling. Data were collected via a closed questionnaire and analyzed using continuum lines and SEM-PLS with SmartPLS for hypothesis testing. Results/findings: The study found a strong organizational culture, effective transformational leadership, and high employee performance. Organizational culture significantly affects performance, while transformational leadership shows a positive but insignificant effect. Conclusions: Organizational culture significantly enhances employee performance, while transformational leadership has a positive but insignificant impact. Limitations: This study uses limited samples and settings, reducing generalizability. External factors and measurement reliability may also affect result validity. Contribution: This study enhances scientific understanding and offers a practical strategy to improve organizational culture quality through transformational leadership aligned with the company’s vision and mission.